Dynamics of low-density ultracold plasmas in externally applied electric and magnetic fields - Wilson, Truman M., author; Roberts, Jacob, advisor; Krueger, David, committee member; Lundeen, Stephen, committee member; Yalin, Azer, committee member (Colorado State University. Libraries, 2013)
The experiments described in this thesis were focused on the influence of external electric and magnetic fields and electron evaporation on the evolution of ultracold plasmas (UCPs). The UCPs were created from the photoionization of 85Rb which was first captured in a magneto-optical trap (MOT) and then magnetically trapped and transferred by a set of magnetic coils attached to a motorized translation stage to a region of the vacuum chamber with a set of electrodes. The first experiment studied the response of the UCP to sharp electric field pulses, which included 2 cycles of a sine wave pulse. These experiments showed a resonant response to the 2 cycles of rf that was density dependent, but was not a collision based mechanism. Instead, the response was caused by a rapid energy transfer to individual electrons through the collective motion of the electron cloud in the UCP. This density-dependent response allowed us to develop a technique for measuring the expansion rate of the UCPs in our system. It was also observed in second set of experiments that electron evaporation from the UCP had a significant effect on the amount of energy that was transferred to the ions to drive the UCP expansion. Model calculations show that we should expect electron evaporation to have a more significant influence on the UCP expansion rate at the relatively low densities of the UCPs that we create compared to other experiments. By modeling electron evaporation during expansion, our data are consistent with evaporation reducing the electron temperature significantly, which lowers the overall UCP expansion rate. In addition to these studies, we also performed an experiment in which it was observed that in the presence of a magnetic field there was a significant increase in the initial UCP expansion rate coupled with a deceleration of the ion expansion at later times in the UCP evolution. Our observations to date are consistent with the magnetic field influencing electron screening and UCP formation. By restricting the electrons motion in the direction transverse to the magnetic field lines to circular orbits around the magnetic field lines, the electrons cannot move appropriately to screen the internal radial electric fields produced by the excess of ions. Studies of this effect are currently under way. Future studies include direct measurements of the electron temperature and collision rates between the components of the UCP as we move towards trapping the UCP in a Penning trap.
Keywords: strong coupling; plasma oscillation; ultracold plasma; evaporative cooling; plasma expansion